Latin America's agricultural exports to China: Recent trends - Jorge Caballero; Ernesto O'Connor; Blanca Amado (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
Latin America is becoming the fastest growing agricultural production region and Brazil has by far the fastest growing agricultural sector. China from being a small agricultural importer (1.4% of world imports in 1990/01), became the fifth largest importer at 5.4% of world imports in 2006/07. China's overall trade with Latin America has expanded substantially during the last two decades -the rate of growth has been greater than any other region in the world since 2005. Most exports from Latin America to China are primary products while Chinese exports to Latin America are mostly industrial products. The Chinese demand for agricultural products is concentrated in food products such as grains and oilseeds. Countries specialised in those commodities -eg. Brazil and Argentina-exhibit a strong orientation on the Chinese market. In turn, growing subsectors in China, like fruits and vegetables, are posing strong competition to some world supplier countries in Latin America such as Chile and Peru. Since China is promoting structural reforms of its agricultural sector, aimed at increasing productivity and improving food security, and is expanding their direct investments overseas to secure provision of raw materials, Latin American governments need to pursue long-run strategic public policies. They need to optimize trade results and promote production efficiency that on one hand contribute to take advantage of the current market situation but at the same time assure the protection of the natural resources and preserve the production capacity and the agricultural diversity.
Keywords: 330; Latin America; China; trade; agriculture; soybean; agricultural policies